Insulin- Therapy in Children Under Five Years. - Hussimy Marchena Morera; Alina Esther González Hermida (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2008)
Diabetes Mellitus Type 1 is one of the chronic diseases with higher prevalence rate in infancy. Insulin-therapy is one of the bases of treatment for these patients. It is a challenge to treat children with diabetes, to choose an appropriate insulin-therapy treatment scheme, to maintain them under a correct metabolic control with the least possible number of hypoglycaemias and with adequate life quality. The objective of this work is to offer some elements linked to insulin-therapy which could be very useful for health workers specifically related with this kind of patients.